Analysis of local habitat selection and large-scale attraction/avoidance based on animal tracking data: is there a single best method? - Mercker, Moritz; Schwemmer, Philipp; Peschko, Verena; Enners, Leonie; Garthe, Stefan (Movement Ecology, 2021)
New wildlife telemetry and tracking technologies have become available in the last decade, leading to a large increase in the volume and resolution of animal tracking data. These technical developments have been accompanied by various statistical tools aimed at analysing the data obtained by these methods.
Gesehen am 20.05.2021